Anthropometric indices are associated with LDL cholesterol in postmenopausal Javanese women (Bangladesh Journal of Medical Science, 2014)
Introduction: Lipid abnormalities are seen to be linked lack of physical activity, obesity, metabolic syndrome and diabetes mellitus. Postmenopausal women experience the changes of body composition by increasing the visceral fat. The study was aimed to explore relationship between anthropometric indices and lipid level in postmenopausal Javanese women. Methods: This cross sectional study included 34 healthy postmenopausal Javanese women, age range between 46-59 years, from Dusun Trukan, Karanggede dan Marangan Prambanan subdistrict, Sleman district. Anthropometric measurements were carried following standard procedure. Appropriate statistical tools were used to analyze data using SPSS Version 17. A p value